SAT0137 Disease Activity Measures Associate Differently with Demographics and Comorbidities in Patients with Rheumatoid Arthritis in Routine Practice Settings. (9th June 2015) - Hwang, Y.G.; Wu, G.; Feng, J.; Lyons, J.; Eng, H.F.; Wisniewski, S.R.; Hwang, C.C.; Sasso, E.H.; Segurado, O.G.; Moreland, L.W.
Abstract : Background: Accurate measurement of disease activity is important for optimal management of patients with rheumatoid arthritis (RA). Better understanding of similarities and differences among the available clinical and biomarker-based disease activity measures may improve their use for therapeutic decision-making. Objectives: Evaluate the relationship between available disease activity indices and their association with other clinical variables. Methods: A cross-sectional analysis was performed for 734 RA patients enrolled in the University of Pittsburgh Rheumatoid Arthritis Comparative Effectiveness Registry (RACER), using all first visits and excluding patients (N=6) who were receiving tocilizumab. Spearman's rank correlation and percentage agreement among 4 disease activity categories (remission, low, moderate, high) were calculated for Disease Activity Score 28 with C-reactive protein (DAS28-CRP), Clinical Disease Activity Index (CDAI), Simplified Disease Activity Index (SDAI), Routine Assessment of Patient Index 3 (RAPID3) and the Multi-biomarker Disease Activity (MBDA) score. Univariate regression analyses were performed to assess association between each disease activity score and American College of Rheumatology (ACR) Core Data Set measures, demographics, and co-morbidities. P-values were adjusted for multiple comparisons using the Benjamini-Hochberg procedure. Results: For 734 patients, mean age and disease duration were 60 and 15 years, respectively. Mean RAPID3, DAS28-CRP, SDAI, CDAI, and MBDA scores were 3.6, 3.3, 15.1, 14.1, and 41.3, respectively. Each disease activity measure was significantly correlated with the others. DAS28-CRP, CDAI, and SDAI correlated strongly with each other (r=0.92–0.99) and to a lesser degree with RAPID3 (r=0.65–0.66) and MBDA score (r=0.35–0.51). Correlation between MBDA score and RAPID3 was lowest (r=0.27). Agreement among categories between DAS28-CRP and CDAI or SDAI was 45% and 56%, respectively, and between CDAI and SDAI was 88%. Agreement between DAS28-CRP and RAPID3 or MBDA score was 47% and 44%, respectively. Agreement between RAPID3 and MBDA score was 38%. All 7 ACR Core measures were significantly associated with disease activity for each index (Figure ). RAPID3 was significantly associated with all measured comorbidities and opiate use; DAS28-CRP, SDAI, and CDAI with fibromyalgia and opiate use; and MBDA score with the Deyo-Charlson comorbidity index. DAS28-CRP, SDAI, and CDAI were not significantly associated with the demographic variables. RAPID3 was significantly associated with race and BMI, and MBDA score with age and BMI. Only MBDA score was significantly associated with seropositivity and not with the Short Form Health Survey (SF12) mental composite score Conclusions: Disease activity indices were significantly correlated with each other and associated with ACR core measures. However, they differed in their relationships with co-morbidities or demographics. These results suggest that disease activity may not be comprehensively assessed by any single composite measure. Disclosure of Interest: Y. G. Hwang: None declared, G. Wu Shareholder of: Myriad Genetics, Inc, Employee of: Crescendo Bioscience, J. Feng: None declared, J. Lyons: None declared, H. Eng: None declared, S. Wisniewski: None declared, C. Hwang Shareholder of: Myriad Genetics, Inc, Employee of: Crescendo Bioscience, E. Sasso Shareholder of: Myriad Genetics, Inc, Employee of: Crescendo Bioscience, O. Segurado Shareholder of: Myriad Genetics, Inc, Employee of: Crescendo Bioscience, L. Moreland: None declared